2021
DOI: 10.1155/2021/9549508
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical and Radiographic Findings among Patients with Traumatic Dental Injuries Seeking Delayed Treatment

Abstract: Background. Time elapsed between trauma and treatment greatly influences the prognosis of traumatic dental injuries (TDIs). The aim of this study was to analyze clinical and radiographic findings related to complications of TDIs among patients seeking delayed treatment of such injuries. Materials and Methods. 123 permanent teeth with a history of previous TDIs were included in the study. Clinical findings analyzed were the type of fracture, type and number of injured teeth, crown discoloration, and pulpal stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…When undertaking an examination following dental trauma, a systematic approach is prudent to reduce the risk of any missed or wrong diagnoses which may negatively impact patient outcomes. 4 A thorough extra-oral and intra-oral hard and soft tissue exam looking for evidence of fractures (e.g. step deformities, mobile segments or embedded tooth fragments) should be undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…When undertaking an examination following dental trauma, a systematic approach is prudent to reduce the risk of any missed or wrong diagnoses which may negatively impact patient outcomes. 4 A thorough extra-oral and intra-oral hard and soft tissue exam looking for evidence of fractures (e.g. step deformities, mobile segments or embedded tooth fragments) should be undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…However, when these resources are unavailable, dentists in private practice assume responsibility for providing after‐hours care. Delayed care for TDIs has been associated with poor prognoses for the affected teeth 8–11 . A study by Vukovic et al 8 compared TDIs to permanent teeth that occurred after‐hours to those during office hours, revealing that 90% of after‐hours injuries experienced a median delay in treatment of 48 h, while injuries during office hours had a median delay of 2.3 h. After‐hours injuries were more likely to result in complications, such as pulpitis, pulp necrosis, internal resorption, or extraction due to pulpal or periodontal complications 12–15 .…”
Section: Introductionmentioning
confidence: 99%
“…Delayed care for TDIs has been associated with poor prognoses for the affected teeth. [8][9][10][11] A study by Vukovic et al 8 compared TDIs to permanent teeth that occurred after-hours to those during office hours, revealing that 90% of after-hours injuries experienced a median delay in treatment of 48 h, while injuries during office hours had a median delay of 2.3 h. After-hours injuries were more likely to result in complications, such as pulpitis, pulp necrosis, internal resorption, or extraction due to pulpal or periodontal complications. [12][13][14][15] Some studies have reported that certain dentists may neglect providing treatment for TDIs in young children.…”
mentioning
confidence: 99%
“…Diagnosis is usually confirmed by radiographic examination which shows complete or partial obliteration of the canal. 2,3 This condition is not pathologic in nature and does not require treatment until and unless radiographic and clinical signs of periapical pathology develop. So it is necessary to observe these teeth both clinically and radiographically before initiating an endodontic treatment.…”
Section: Introductionmentioning
confidence: 99%